Respuestas
Respuesta dada por:
0
(a)
![y=\dfrac{(1-3x)^2}{1-x}\\ \\ \\
y'=\dfrac{-3\cdot 2(1-3x)-(1-3x)(-1)}{(1-x)^2}\\ \\ \\
y'=\dfrac{-5+15x}{(1-x)^2} y=\dfrac{(1-3x)^2}{1-x}\\ \\ \\
y'=\dfrac{-3\cdot 2(1-3x)-(1-3x)(-1)}{(1-x)^2}\\ \\ \\
y'=\dfrac{-5+15x}{(1-x)^2}](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B%281-3x%29%5E2%7D%7B1-x%7D%5C%5C+%5C%5C+%5C%5C%0Ay%27%3D%5Cdfrac%7B-3%5Ccdot+2%281-3x%29-%281-3x%29%28-1%29%7D%7B%281-x%29%5E2%7D%5C%5C+%5C%5C+%5C%5C%0Ay%27%3D%5Cdfrac%7B-5%2B15x%7D%7B%281-x%29%5E2%7D)
(b)
![y=3\sqrt{x}+\dfrac{3}{x}\\ \\ \\
y'=\dfrac{3}{2\sqrt{x}}-\dfrac{3}{x^2} y=3\sqrt{x}+\dfrac{3}{x}\\ \\ \\
y'=\dfrac{3}{2\sqrt{x}}-\dfrac{3}{x^2}](https://tex.z-dn.net/?f=y%3D3%5Csqrt%7Bx%7D%2B%5Cdfrac%7B3%7D%7Bx%7D%5C%5C+%5C%5C+%5C%5C%0Ay%27%3D%5Cdfrac%7B3%7D%7B2%5Csqrt%7Bx%7D%7D-%5Cdfrac%7B3%7D%7Bx%5E2%7D)
(b)
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años